Transformasi Perilaku Konsumtif di Era E-Commerce: Antara Kenyamanan Digital dan Tantangan Konsumsi Berlebihan Menurut Ekonomi Islam - Khisan, Zariatul; Aqlani, Muhammad Indra Zul (Universitas Islam Lamongan, 2025)
The rapid growth of e-commerce in Indonesia offers convenience and broad access to digital shopping but also triggers excessive consumerism, which conflicts with Islamic economic principles. This study focuses on the transformation of consumer behavior in the e-commerce era from an Islamic perspective, emphasizing the need to shift from excessive consumption (israf) toward productive economic activities aligned with Sharia values. Using a qualitative approach, the research analyzes literature and case studies related to consumer behavior, digital financial innovations, and Sharia economic integration. Findings reveal that addressing overconsumption requires early Islamic financial education, strict Sharia-compliant regulations, and promotion of simple, production-based consumption patterns. Strengthening the role of Sharia micro, small, and medium enterprises (MSMEs), government incentives, and financial institutions’ support are crucial to fostering a balanced and sustainable economy. Additionally, controlling aggressive digital marketing and fostering collaboration between society and government are essential to build a healthy Sharia economic ecosystem. This holistic approach aims to create economic balance, social welfare, and blessings in accordance with Islamic teachings, helping consumers avoid debt and waste while encouraging productive contributions to society.